Relationship between Anthropometric Profiles and Performance of Gymnastics Athletes (Universitas Pendidikan Indonesia, 2024)
Gymnastics is one of the sports requiring the right composition of body posture to support its best performance. For this reason, coaches and athletes should know anthropometric profiles to improve their performance in championships. This study aimed to analyze the effect of anthropometric profiles on the performance of gymnastics athletes. This research is correlation research involving 17 youth gymnastic athletes in West Java (average age of 19.7). The sampling technique used the saturated sampling technique. The instruments included anthropometric measurement tests and gymnastics performance tests referring to the Code of Points (COP) set by the International Federation of Gymnastics (FIG). The results showed that there was a significant correlation between anthropometric profiles and the athlete performance. The effects of anthropometric correlation variables were height of 0.678, weight of 0.487, BMI of -0.777, LiLA of 0.605, and abdominal circumference of -0.513. The results obtained the significance level of height on exercise performance of .003 0.05, body weight on exercise performance of .047 0.05, BMI on exercise performance of 0 0.05, upper arm circumference on exercise performance of .010 0.05, and circumference of abdomen on exercise performance of .035 0.05. This study concludes that there is a significant effect of anthropometric profiles on the performance of gymnastics athletes.